Ceramic-Based 3D Printed Supports for Photocatalytic Treatment of Wastewater. (10th July 2017) - Hernández-Afonso, Lorena; Fernández-González, Ricardo; Esparza, Pedro; Borges, M. Emma; Díaz González, Selene; Canales-Vázquez, Jesús; Ruiz-Morales, Juan Carlos
Abstract : 3D printing technology has become a powerful tool to produce 3D structures in any type of materials. In this work, 3D printing technology is used to produce 3D porous structures in CaSO4 which can be later activated with an appropriate photocatalyst. TiO2 was selected as an ideal photocatalyst producing activated 3D structures which can be used to study their effectiveness in the degradation of pollutants in wastewater. Methylene blue was used as a model molecule in these studies. The photocatalytic studies showed that TiO2 -activated 3D structures using nanoparticles of SiO2 in the process produce more than 50% of conversion of methylene blue in just 1 h of irradiation and almost 90% in 5 h.